Syrian immigrants in Turkey: services, satisfaction and suggestions for policy-making - Özgüzel, Seyfi (2019)
Due to the 8 years’ war in Syria, Turkey faced the immigration of more than 3.5 million Syrian refugees. About a million of them are settled in the region Çukurova. Allthough most of them do not have a permanent residence permit it may be expected that a vast number of these Syrian migrants will settle permanently. The majority of this immigrant population is non or low-educated; they rarely participate in education programmes and intercultural communication disorders with the local community and societal tensions occur. Surveys have been conducted among adult Syrian immigrants living in Çukurova in order to identify whether their satisfaction about local services. Secondly, services and communication strategies of public institutions, municipalities and NGOs in the Adana, the main city in the region have been analysed in order to identify the range and effects of their services. Assuming that a lack of integration and intercultural communication disorders cause disturbance in the local communities, this study aims to investigate possible solutions - with the use of the integration policy of the Netherlands – in order to prevent societal unrest.